1975
DOI: 10.1080/10236247509378510
|View full text |Cite
|
Sign up to set email alerts
|

The detection, location and recognition of food by juvenile banana prawns,Penaeus merguiensisde man

Abstract: Penaeus merguiensis detects food and discriminates it from non-food particles by chemosensory mechanisms. Vision was not found to play any part in the process. Food seeking behaviour is initiated by low concentrations of organic compounds (10 -5 -10 -6 Molar solutions of a range of amino acids) in the water, but higher concentrations (10 -1 -10 -2 M) are needed to produce a masticating reaction by the mouthparts. The stimuli for mouthpart action and food seeking behaviour are not specific, the responses result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…Whilst work on fish has shown that betaine significantly reinforces the chemoattractant effect of feeds, leading to increased ingestion (Carr andChaney 1976, Carr et al 1977), no similar indication of any one aminoacid attractant has been shown for juvenile crustaceans (Hindley 1975, Ache 1982. Several amino acids, similar to those used in the present study (Table 3), are frequently reported to act as stimulants (Laverack 1963, Case 1964, Carr 1978), but no clear hierarchy exists amongst the amino acids tested.…”
Section: Discussionmentioning
confidence: 54%
“…Whilst work on fish has shown that betaine significantly reinforces the chemoattractant effect of feeds, leading to increased ingestion (Carr andChaney 1976, Carr et al 1977), no similar indication of any one aminoacid attractant has been shown for juvenile crustaceans (Hindley 1975, Ache 1982. Several amino acids, similar to those used in the present study (Table 3), are frequently reported to act as stimulants (Laverack 1963, Case 1964, Carr 1978), but no clear hierarchy exists amongst the amino acids tested.…”
Section: Discussionmentioning
confidence: 54%
“…Although I agree with this conclusion, ambiguity exists because these compounds were the only ones tested in most studies (e.g. Shelton and Mackie 197 1;Mackie 1973;Fuzessery and Childress 1975;Hindley 1975;Carr 1978;Carter and Steele 1982;Robertson et al 198 1;Zimmer-Faust and Case 1982a;Johnson and Atema 1986;Harpaz et al 1987;Tierney and Atema 1988). In fact, laboratory investigations have been performed on individuals of only four crustacean species whose behavioral responses were assayed for both low-and highmolecular-mass fractions of prey extracts or body odors.…”
Section: Perception Of Chemical Qualitymentioning
confidence: 70%
“…In the first, chemicals readily available in purified form have been assayed without parallel tests of substances prepared from prey tissues (e.g. McLeese 1970; Shelton and Mackie 197 1;Hindley 1975;Ache et al 1978;Johnson and Atema 1986;Harpaz et al 1987;Tierney and Atema 1988). Such studies have been valuable in determining effects of molecular structure on attractivity, but their 1367 applicability to ecological investigations is limited.…”
Section: Methods Used In Preparing Chemical Stimulimentioning
confidence: 99%
“…Previous work on chemoreception in pelagic crustaceans has focussed on its role in food detection (Hindley, 1975;Hamner and Hamner,1977;Busdosh et al1982;Hamner et al,1983). Hyperiid amphipods utilize salps for food, shelter and depositing their young (Fig.…”
Section: Behavioral Bioassaymentioning
confidence: 99%
“…The interpretation of function is not usually possible on morphological grounds alone but will depend partly on the microenvironment in which the sensilla are situated. For example, Hindley (1975) mapped particular areas on the body of a decapod Penaeus merguiensis that exhibited a chemosensitivity to meat extract. However, if one combines the morphology of sensilla along with their location on the body, their ultrastructure and physiology and the behavior of the organism, their function can be deduced.…”
Section: Introductionmentioning
confidence: 99%